EFEK KECERDASAN EMOSI DAN KEPUASAN KOMUNIKASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN - Pusparani Ratna Dwisara; Ita Juwitaningrum; Diah Zaleha Wyandini (JURNAL PSIKOLOGI INSIGHT, 2018)
This study aimed to determine the influence of emotional intelligence and communication satisfaction of organizational citizenship behavior of employees. This research used quantitative approach with correlational methods. The participants of this research was 300 employees in Bandung. The instruments were emotional intelligence (Goleman that modified by Muta’asifah (2013), communication satisfaction (Downs and Hazen, 1977), and organizational citizenship behavior (Kumar and Shah, 2015). The analysis of this research was multiple linier regression analysis. The result of this research showed that there is a effect of emotional intelligence and communication satisfaction on organizational citizenship behavior of employees in Bandung. In order to improve the aspects of this research that are still lacking, it is necessary to conduct training and counseling on employees.